Instability Induced by Cross-Diffusion in a Predator-Prey Model with Sex Structure - Shengmao Fu; Lina Zhang (Journal of Applied Mathematics)
In this paper, we consider a cross-diffusion predator-prey model with sex structure. We prove that cross-diffusion can destabilize a uniform positive equilibrium which is stable for the ODE system and for the weakly coupled reaction-diffusion system. As a result, we find that stationary patterns arise solely from the effect of cross-diffusion.